Dynamics of Conflict on Women’s Rights to Land under Customary Tenure: Effectiveness of Legislation - Uganda Women’s Network (Uganda Women’s Network, 2010)
Women’s land rights are protected under Uganda’s 1995 Constitution and the Land Act of 1998, which defines the types of land ownership that are legally recognized. Both clearly spell out women’s right to access and own land whether individually or with others. The Land Act also seeks to protect women’s rights by including their recognition and consent before any transactions involving family land. Customary tenure practices are also required to involve women in significant land decision making.